Germline variants impact on somatic events during tumorigenesis - Ramroop, Johnny R. (Trends Genet, 2019)
Cancer is characterized by diverse genetic alterations in both germline and somatic genomes that disrupt normal biology and providea selective advantage to cells during tumorigenesis. Germline and somatic genomes have been extensively studied independently, leading to numerous biological insights. Analyses integrating data from both genomes have identified genetic variants impacting somatic events in tumors, including hotspot driver mutations. Interactions among specific germline variants and somatic eventsinfluence cancer subtypes, treatment response, and clinical outcomes. Investigation of these complex interactions is increasing our understanding of aberrant pathwaysin tumorsthat may uncover novel therapeutic targets. Here, we review the literature describing the role germline genetic variantsplay in promoting selection of and generation of specific mutations during tumorigenesis.